2014
DOI: 10.1158/1078-0432.ccr-13-3205
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Low-Dose IL-2 for GVHD Prophylaxis after Allogeneic Hematopoietic Stem Cell Transplantation Mediates Expansion of Regulatory T Cells without Diminishing Antiviral and Antileukemic Activity

Abstract: Purpose Graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (alloSCT) has been associated with low numbers of circulating CD4+CD25+FoxP3+ regulatory T-cells(Tregs). Because Tregs express high levels of the IL-2 receptor, they may selectively expand in vivo in response to doses of IL-2 insufficient to stimulate T-effector T-cell populations, thereby preventing GvHD. Experimental Design We prospectively evaluated the effects of ultra low-dose (ULD) IL-2 injections on Treg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 38 publications
11
150
0
2
Order By: Relevance
“…13 These data indicated that even though IL-2 could prevent cGVHD, relapse is still an important problem that should be addressed. Consistent with previously published data, 14,15 we found that NK and Treg cells had profoundly expanded in patients receiving IL-2 treatment. In addition, the data showed that the incidence of cGVHD was decreased after IL-2 treatment.…”
Section: Discussionsupporting
confidence: 92%
“…13 These data indicated that even though IL-2 could prevent cGVHD, relapse is still an important problem that should be addressed. Consistent with previously published data, 14,15 we found that NK and Treg cells had profoundly expanded in patients receiving IL-2 treatment. In addition, the data showed that the incidence of cGVHD was decreased after IL-2 treatment.…”
Section: Discussionsupporting
confidence: 92%
“…But excessive exposure to IL-2 due to very low CsA concentrations may compromise Treg expansion. This assumption is also supported by some studies establishing that only ultralow doses of IL-2 are necessary to a better expansion of Treg (35)(36)(37).…”
Section: Application To New Patientsmentioning
confidence: 69%
“…New indication of IL-2 for immune tolerance was proposed from the field of HSCT and thereafter extending to the field of autoimmunity within just a few years, suggesting the study of clinical GVHD could be an important platform to develop new cellular therapy for No grade II-IV aGVHD [34] GVHD prophylaxis 1 × 10 6 IU/m 2 /day, daily administration for 14 days followed by a 14-day hiatus, from day 60…”
Section: Resultsmentioning
confidence: 99%
“…Huston group first tested the effect of prophylactic IL-2 for pediatric patients after HSCT [34]. IL-2 (1-2 × 10 5 IU/ m 2 /day) was daily administrated from days 30 to 120, which resulted in Treg increase in the first month after the initiation of IL-2.…”
Section: Prophylactic Intervention In Treg Homeostasis By Low-dose Il-2mentioning
confidence: 99%